2018
DOI: 10.1371/journal.pone.0192396
|View full text |Cite
|
Sign up to set email alerts
|

Associations of hyperuricemia and obesity with remission of nonalcoholic fatty liver disease among Chinese men: A retrospective cohort study

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a common chronic disease that is associated with high serum uric acid (SUA) levels, although the effects of high SUA levels on NAFLD remission remain unclear. In addition, it is unclear whether obesity and high SUA levels have a combined effect on NAFLD remission. This retrospective cohort study evaluated male employees of seven Chinese companies and investigated the association between high SUA levels and NAFLD remission, as well as the potential combined effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…Another study by Wang et al [ 15 ] reported a positive relationship between BMI and SUA levels among healthy individuals in Jiangsu province of China. In more recent studies, a significant positive relationship was observed between SUA levels and obesity in population of China [ 21 , 22 , 23 , 24 ], Japan [ 25 ], India [ 7 , 26 ], Pakistan [ 27 ] Iraq [ 28 ] and United States [ 43 ]. Although a positive association between obesity and SUA levels has been reported in previous studies; the mechanism by which how uric acid is increased in obesity has not well elucidated yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study by Wang et al [ 15 ] reported a positive relationship between BMI and SUA levels among healthy individuals in Jiangsu province of China. In more recent studies, a significant positive relationship was observed between SUA levels and obesity in population of China [ 21 , 22 , 23 , 24 ], Japan [ 25 ], India [ 7 , 26 ], Pakistan [ 27 ] Iraq [ 28 ] and United States [ 43 ]. Although a positive association between obesity and SUA levels has been reported in previous studies; the mechanism by which how uric acid is increased in obesity has not well elucidated yet.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperuricemia and its relation with obesity have been documented in previous studies. A significant positive association has been found between SUA and obesity in the adult population of China [ 21 , 22 , 23 , 24 ], Japan [ 25 ], India [ 7 , 26 ], Pakistan [ 27 ] and Iraq [ 28 ]. However, there is a lack of studies on the association between obesity and SUA for the Bangladeshi population.…”
Section: Introductionmentioning
confidence: 99%
“…Nonalcoholic fatty liver disease (NAFLD) was diagnosed based on abdominal ultrasonography findings plus the exclusion of alcohol consumption, viral infection, or autoimmune liver disease. 22 Abdominal ultrasonography found at least two manifestations that could diagnose NFALD, including diffusely increased echogenicity (''bright'') liver with liver echogenicity greater than kidney or spleen, vascular blurring, and deep attenuation of ultrasound signal. 23…”
Section: Methodsmentioning
confidence: 99%
“…Experimental Design [28][29] The rats were randomly divided into three groups consisting of each 6 rats each as follows:…”
Section: Introductionmentioning
confidence: 99%